2021
DOI: 10.1063/5.0038628
|View full text |Cite
|
Sign up to set email alerts
|

High Mg activation in implanted GaN by high temperature and ultrahigh pressure annealing

Abstract: We demonstrate high p-type conductivity and hole concentrations >1018 cm−3 in Mg-implanted GaN. The implantation was performed at room temperature and by post-implantation annealing at 1 GPa of N2 and in a temperature range of 1200–1400 °C. The high pressure thermodynamically stabilized the GaN surface without the need of a capping layer. We introduce a “diffusion budget,” related to the diffusion length, as a convenient engineering parameter for comparing samples annealed at different temperatures and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…For N a = 2.8 × 10 17 cm −3 , we obtain R = N a /[Mg] = 2.8 × 10 17 cm −3 /(2.9 × 10 17 cm −3 ) ≈ 96.6%, which is consistent with those reported previously. 23,27,28,31) Furthermore, Fig. 5(c) indicates that by the suitable optimization of N a , a BV of more than 650 V can be realized without FLRs, which has already been demonstrated experimentally.…”
supporting
confidence: 56%
“…For N a = 2.8 × 10 17 cm −3 , we obtain R = N a /[Mg] = 2.8 × 10 17 cm −3 /(2.9 × 10 17 cm −3 ) ≈ 96.6%, which is consistent with those reported previously. 23,27,28,31) Furthermore, Fig. 5(c) indicates that by the suitable optimization of N a , a BV of more than 650 V can be realized without FLRs, which has already been demonstrated experimentally.…”
supporting
confidence: 56%
“…But here again it´s not about photoluminescence. Mg doping in relation with GaN:Eu has been investigated by several other groups as well 47 51 , as the Mg co-doping is supposed to increase the photoluminescence (PL) as well as the electroluminescence intensity. Hoang 52 investigated defect physics of Eu-doped GaN using first-principles hybrid density-functional.…”
Section: Introductionmentioning
confidence: 99%
“…Using this technique, the implantation-induced strain is effectively removed, [12] and high acceptor activation percentages greater than 80% respective to implanted magnesium (Mg) ions have been obtained. [10,13,14] Unfortunately, prolonged annealing at high temperatures can promote the diffusion of Mg atoms so that the dopant dispersion profile is changed. [10,[13][14][15] Sakurai et al [15] reported that the diffusion coefficient for Mg atoms in GaN was 30 times larger than that for Mg in epitaxially grown Mg-doped GaN.…”
Section: Introductionmentioning
confidence: 99%
“…[10,13,14] Unfortunately, prolonged annealing at high temperatures can promote the diffusion of Mg atoms so that the dopant dispersion profile is changed. [10,[13][14][15] Sakurai et al [15] reported that the diffusion coefficient for Mg atoms in GaN was 30 times larger than that for Mg in epitaxially grown Mg-doped GaN. This finding suggests that dopant diffusion is enhanced by the formation of point defects during implantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation